Value proposition for improved groundnut seed in Tanzania: Why and how to increase it - Rutsaert, Pieter; Donovan, Jason A.; Daudi, Happy (CGIAR, 2024)
This brief explores the value proposition for farmers in Tanzania to invest in improved groundnut seed and the related implications for seed systems development. In late 2023–early 2024, we conducted 21 focus-group discussions and interviews with farmer groups, processors, traders, and seed producers. Our findings suggested that the current value proposition for improved seed was insufficient to encourage uptake at scale of improved seed. Farmers planted groundnut on poor soils, with little use of fertilizers or soil improvement conditioners. Brokers and traders purchased groundnuts in pods at the same price, regardless of size, color, or variety. While improved seed existed in limited volumes, the relatively high cost of the seed, combined with the lack of incentives for quality, meant that most farmers recycled their seed or purchased grain for use as seed. The success of future strategies to increase the impact from groundnut breeding hinges on farmers obtaining a higher value proposition from improved groundnut seed. The focus must be broader than seed systems development, encompassing long-term public and private sector investments in developing the peanut butter value chain, combined with investments in improving the agronomic conditions farmers face.